Nietzsche’s speculative pragmatism - Hickmann, Gabriel Cunha (Universidade do Vale do Rio dos Sinos, 2025)
This work proposes a reassessment of Nietzsche’s philosophical significance through an engagement with contemporary thought and the aporias of the present. By reconstructing Nietzsche’s perspectivism—situating it within his broader intellectual framework and its dialogue with the philosophical tradition (particularly critiques of Kantian idealism)—we demonstrate how this stance, more nuanced than often assumed, resists traditional misinterpretations, especially those advanced by Critical Theory. Our analysis reveals that Nietzsche’s work converges with a speculative pragmatist position, a term employed by thinkers like Isabelle Stengers to describe their own theoretical approaches. This recontextualization not only clarifies Nietzsche’s methodological commitments but also illuminates underappreciated affinities between his thought and contemporary debates. Finally, we trace how Nietzschean ideas resonate in current philosophy, arguing that these developments, if we are right, shed new light on the broader implications of Nietzsche’s philosophical project in a broad sense.

Questo lavoro propone una rivalutazione del significato filosofico di Nietzsche attraverso un confronto con il pensiero contemporaneo e le aporie del presente. Ricostruendo il suo prospettivismo—collocandolo all’interno del suo quadro intellettuale più ampio e del suo dialogo con la tradizione filosofica (in particolare le critiche all’idealismo kantiano)—dimostriamo come questa posizione, più sfumata di quanto spesso si assuma, resista alle interpretazioni tradizionali, specialmente quelle avanzate dalla Teoria Critica. La nostra analisi rivela che l’opera di Nietzsche converge con una posizione pragmatista speculativa, un termine utilizzato da pensatori come Isabelle Stengers per descrivere i propri approcci teorici. Questa ricontestualizzazione non solo chiarisce gli impegni metodologici di Nietzsche, ma illumina anche affinità sottovalutate tra il suo pensiero e i dibattiti contemporanei. Infine, tracciamo come le idee nietzscheane risuonino nella filosofia attuale, sostenendo che questi sviluppi, se la nostra tesi è corretta, gettino nuova luce sulle implicazioni più ampie del progetto filosofico di Nietzsche in senso lato.
Keywords: Nietzsche; Teoria Crítica; Pragmatismo; Filosofia contemporânea; Filosofia moderna; Critical theory; Pragmatism; Contemporary philosophy; Modern philosophy; ACCNPQ::Ciências Humanas::Filosofia